Cobalt Quaterpyridine Complexes for Highly Efficient Heterogeneous CO2 Reduction in Aqueous Media. Issue 34 (22nd July 2022) - Sun, Libo; Reddu, Vikas; Xi, Shibo; Dai, Chencheng; Sheng, Yuan; Su, Tan; Fisher, Adrian C.; Wang, Xin
Abstract: Ligands play a critical role in the electrocatalytic CO2 reduction reaction (CO2 RR) based on heterogeneous molecular catalysts. Previous research on heterogeneous molecular electrocatalysis has mainly dealt with N4 ligands with pyrrole as subunits (porphyrin, phthalocyanine, etc.), while ligands constructed from pyridine subunits remain uncommon. The examples for comparing active configurations are few and far between. Herein, the development of new N4 cobalt complexes based on pyridine subunits is explored. After anchoring onto carbon nanotubes, they can exhibit CO2 RR activity at a low overpotential of 140 mV, and high activity from ‐0.30 to ‐0.60 V versus reference hydrogen electrode with a selectivity of above 98%. Excellent performance at large current densities can also be observed in a flow cell. In situ attenuated total reflectance‐Fourier transform infrared spectroscopy proves that such electrocatalysts exhibit CO production at lower overpotential and moderate CO adsorption ability over a wide potential range. From density functional theory calculations, it is shown that a pyridine‐based cobalt complex on a carbon substrate can reduce the Gibbs free energy for reactions further than its counterpart pyrrole‐based ones. Further analysis proves that the semimetal behavior of optimized d‐orbitals may facilitate charge transfer and increase the activity. This provides a new insight for understanding catalytically active moieties in heterogeneous molecular catalysts with ligands constructed from pyridine subunits. Abstract : New series of N4‐structure cobalt quaterpyridine complexes constructed from pyridine subunits are synthesized for heterogeneous electrocatalytic CO2 reduction in aqueous media. When immobilized onto carbon nanotubes, remarkably enhanced activity and selectivity are obtained for such electrocatalysts when compared with their counterpart cobalt porphyrin and phthalocyanine derivatives based on pyrrole subunits.